Mobility may impact attention abilities in healthy term or prematurely born children at 7-years of age: protocol for an intervention controlled trial - Hadrien Ceyte; Joëlle Rosenbaum; Isabelle Hamon; Maëlle Wirth; Sébastien Caudron; Jean-Michel Hascoët (BMC, 2018)
Abstract Background Seven years of age is a milestone for learning basic knowledge that is strongly related to attention abilities such as Alerting, Orienting, and Inhibition function, allowing for appropriate adaptation to primary school. These attention abilities are also influenced by gestational age at birth in a complex manner, indicating an area of weakness in prematurely born children. Furthermore, recent studies suggest that allowing children to have freedom of movement during learning may improve their attention level and school performance. The purpose of the present study is to determine the influence of mobility on the attentional components that may impact learning abilities in children aged 7-years who were born at term and prematurely. Methods This prospective, randomized, controlled trial will focus on psychometric testing of attentional abilities assessed with the Attention Network Test for Child (Child ANT) and involves a mixed measurement design. Forty-eight children aged 7-years, half of whom were premature at birth and in their expected grade without learning difficulties will be included after parental consent. They will be equipped with a head-mounted display in which the Child ANT will be presented. The association of different flankers and pre-cues will allow the measurement of the development level of Alerting, Orienting, and Inhibition function. The task will be composed of one experimental block of trials randomly performed per posture: seated, standing, or free. Discussion This study will assess the contribution of mobility in specific attentional contexts that are usually present during fundamental learning in children. New pedagogical formats of teaching could consider these findings, and new pedagogical tools enabling free spontaneous child mobility might be designed. Moreover, a small percentage of children integrating into the educational system are born prematurely. These children, often considered immature and hyperactive, could benefit from educational innovations that enhance their attention abilities, thereby improving their adaptation to primary school. Trial registration This trial is registered at ClinicalTrials.gov (NCT03125447).